2021
DOI: 10.5694/mja2.51039
|View full text |Cite
|
Sign up to set email alerts
|

National Heart Foundation of Australia: position statement on coronary artery calcium scoring for the primary prevention of cardiovascular disease in Australia

Abstract: ardiovascular disease (CVD) is a leading cause of death in Australia 1 and contributes to a significant health care burden. 2 Australian guidelines for management of CVD risk in primary prevention recommend the assessment of absolute CVD risk, using the algorithm developed by the National Vascular Disease Prevention Alliance (NVDPA), which calculates an individual's risk of a CVD event over a 5-year period. 3 Additional risk modifiers, such as coronary artery calcium (CAC) scoring, have been investigated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The CAC score was measured using Agatston (standard Agatston CAC score). Studies have shown that CAC scores are independently associated with ASCVD events [ 36 ]. Nixdorf et al showed that patients with CAC scores > 400 are expected to have a 10-year incidence of ASCVD events of 13.50% [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CAC score was measured using Agatston (standard Agatston CAC score). Studies have shown that CAC scores are independently associated with ASCVD events [ 36 ]. Nixdorf et al showed that patients with CAC scores > 400 are expected to have a 10-year incidence of ASCVD events of 13.50% [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the CAC score is a continuous variable, guidelines recommend a CAC score of ≄ 100 Agatston units as a threshold for initiating statins [4][5][6]. The automated model accurately identified a CAC score >100 Agatston units in 95% of individuals compared with manual human assessment.…”
Section: Bolded Entries Represent Agreement In Classificationmentioning
confidence: 98%
“…Re-direction of the human operator's role to other tasks instead can further reduce costs associated with CAC scoring, thus making it more widely available. This is important as demand for CAC scoring is likely to increase substantially in the future due to guidelines now recommending its use as an additional non-invasive tool for cardiovascular risk-stratification [4][5][6]. Furthermore, automated models can be applied to large populations for screening or research purposes due to their ability to quantify CAC in seconds and because AI can potentially overcome measurement errors by human observers due to high repeatability [21,23].…”
Section: Bolded Entries Represent Agreement In Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent position statements by the Cardiac Society of Australia and New Zealand (CSANZ) 7 and the National Heart Foundation (NHF) 8 reflect CAC recommendations in overseas guidelines, but note that local information on outcomes and cost‐effectiveness is limited. A United States study found that statin treatment guided by CAC scores may be more cost‐effective than standard predicted risk thresholds, and that adherence to therapy is an important contributor to its benefit 9 …”
mentioning
confidence: 99%